2010
DOI: 10.3402/ljm.v5i0.5266
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of somatisation and psychologisation among patients visiting primary health care centres in the State of Qatar

Abstract: BackgroundMedically unexplained somatic complaints are among the most common clinical presentations in primary care in developing countries and they are considerable burden for patients and health care system.ObjectivesThe aim of this study was to determine the prevalence of somatisation in comparison to psychologisation among a sample of Qatari patients who were visiting primary health care (PHC) centres and to investigate the clinical and socio-demographic characteristics of somatisers (STs) and psychologise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Our finding of a peak age for depression and anxiety disorders during midlife is in keeping with other epidemiological findings in the State of Qatar and other Western countries. [ 9 13 16 34 35 36 37 38 39 ] More recently a study reported[ 13 ] that the widely documented decrease in the prevalence of mental depression episode among the elderly is much more pronounced in developed than in developing countries. Although the prevalence of chronic physical conditions increased with age in both developed and developing countries, the association between depression and chronic conditions generally decreases with age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our finding of a peak age for depression and anxiety disorders during midlife is in keeping with other epidemiological findings in the State of Qatar and other Western countries. [ 9 13 16 34 35 36 37 38 39 ] More recently a study reported[ 13 ] that the widely documented decrease in the prevalence of mental depression episode among the elderly is much more pronounced in developed than in developing countries. Although the prevalence of chronic physical conditions increased with age in both developed and developing countries, the association between depression and chronic conditions generally decreases with age.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 31 32 ] It is worthwhile noting that in two other Middle East populations, conversion disorder has also been reported to be high in primary care in Israel,[ 14 34 35 ] in general practice attendees across Europe[ 36 37 38 39 ] and in Qatar. [ 16 31 32 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, 75% of patients presenting to primary care clinics in the United Kingdom with unexplained physical symptoms were found to be females [12]. Other reports from Middle Eastern countries also indicated a female predominance of SD [8][9][10]. This difference in gender distribution may be attributed to several factors.…”
Section: Discussionmentioning
confidence: 96%
“…[ 3 ] Somatization diagnosis is a prevalent, expensive, and a difficult-to-treat problem for general practitioners. [ 4 ] It is also reported that some cultures stigmatize psychological disorder more than others. [ 5 ] To overcome the confusion around the term somatization, many researchers prefer the term medically unexplained physical symptoms (MUPS).…”
Section: Introductionmentioning
confidence: 99%